Rhinosinusitis pada Kanguru Abu–Abu Timur (Magropus giganteus) di Taman Safari Indonesia II Jawa Timur : Rhinosinusitis in East Gray Kanguru (Magropus giganteus) in Taman Safari Indonesia II Jawa Timur - Muhammad Fachrur Rodzy Zaenudin; Endang Endrakasih; Wahyuningsih Wahyuningsih (Politeknik Pertanian Bogor, 2023)
Rhinosinusitis is an inflammation of the nasal mucosa and paranasal sinuses, accompanied by two or more symptoms, one of which is nasal blockage/obstruction/congestion) or nasal discharge (anterior/posterior nasal drip). Anamnesis, recording of signals, clinical examination, laboratory examination (complete hematological examination and Gram staining of mucopurulent nasal secretions) and Sinar–X were performed on Nobel kangaroo. Regarding the anamnesis and physical/clinical examination, the Nobel kangaroo in Australiana Zone TSI II was seen to have mucopurulent secretions on its nose and decreased activity. After hematological examination of the blood, Gram staining of mucopurulent nasal secretion bacteria, and supporting examinations in sinar–X examination, the Nobel kangaroo was diagnosed with rhinosinusitis caused by a bacterial infection. The prognosis for this case is Fausta – dubious. Fausta with treatment, dubious if no rhinosinusitis surgery is done. Handling/therapy is administered by antibiotic therapy, nebulizer/steam therapy, multivitamins, and multi-minerals were given orally and inhalation.